Whales in warming water: Assessing breeding habitat diversity and adaptability in Oceania's changing climate. (13th February 2019) - Derville, Solène; Torres, Leigh G.; Albertson, Renee; Andrews, Olive; Baker, C. Scott; Carzon, Pamela; Constantine, Rochelle; Donoghue, Michael; Dutheil, Cyril; Gannier, Alexandre; Oremus, Marc; Poole, Michael M.; et al.
Abstract: In the context of a changing climate, understanding the environmental drivers of marine megafauna distribution is important for conservation success. The extent of humpback whale breeding habitats and the impact of temperature variation on their availability are both unknown. We used 19 years of dedicated survey data from seven countries and territories of Oceania (1, 376 survey days), to investigate humpback whale breeding habitat diversity and adaptability to climate change. At a fine scale (1 km resolution), seabed topography was identified as an important influence on humpback whale distribution. The shallowest waters close to shore or in lagoons were favored, although humpback whales also showed flexible habitat use patterns with respect to shallow offshore features such as seamounts. At a coarse scale (1° resolution), humpback whale breeding habitats in Oceania spanned a thermal range of 22.3–27.8°C in August, with interannual variation up to 2.0°C. Within this range, both fine and coarse scale analyses of humpback whale distribution suggested local responses to temperature. Notably, the most detailed dataset was available from New Caledonia (774 survey days, 1996–2017), where encounter rates showed a negative relationship to sea surface temperature, but were not related to the El Niño Southern Oscillation or the Antarctic Oscillation from previous summer, a proxy for feeding conditions that may impact breeding patterns. Many breeding sites that are currently occupied are predicted to become unsuitably warm for this species (>28°C) by the end of the 21st century. Based on modeled ecological relationships, there are suitable habitats for relocation in archipelagos and seamounts of southern Oceania. Although distribution shifts might be restrained by philopatry, the apparent plasticity of humpback whale habitat use patterns and the extent of suitable habitats support an adaptive capacity to ocean warming in Oceania breeding grounds. Abstract :